Discussing democracy in Spain and in Latin America during the age of revolutions: commonalities and differences. Issue 2 (3rd May 2020) - Fernández-Sebastián, Javier
ABSTRACT: This article provides an overview of the early uses of the term democracy in Spain and in Hispanic America during the 19th century. It is mainly built on the collaborative research conducted in the region in the field of conceptual history in recent years, especially on the publications of the Iberconceptos network. By grouping all the Spanish-speaking countries of the Western Hemisphere into a single block, my comparative approach is schematic, for it is clear that this part of the world is far from being a homogeneous sociopolitical space. Even so, the contrast between the two poles – Spain and Latin America – has proved to be heuristically productive, since it enables us to identify certain similarities and differences between the respective conceptualizations and practices associated with democracy that occurred on both sides of the Atlantic between 1808 and 1875, approximately. From some common features, patterns and milestones that this essay reveals it is possible to draw a schematic chronology that could serve as a general framework to subsequent more specific historical studies on the evolution of the concept of democracy in this or that particular country belonging to this cultural area.